Global trends in halal animal-based products: a comprehensive review of consumer demand, supply chain dynamics, and market opportunities - Kristanti, Novita Dewi; Puspita, Dewi Fatma Dwi; Hilmi, Ilham; Nurhadira; Rizki, Muhammad Zidan Fatkhur; Alamsyah, Muhammad Teddy (Universitas Airlangga, 2025)
The global halal industry, particularly in animal-based products such as meat and dairy, is rapidly expanding due to the growing Muslim population and greater consumer attention to product quality. However, challenges such as inconsistent certification systems and contamination risks hinder market growth and consumer trust. The purpose of this research is to examine the worldwide landscape of halal animal-based products, focusing on consumer demand, supply chain capacity, sustainability challenges, and market opportunities. The main objective is to identify patterns and trends related to halal product demand and supply chain sustainability. A systematic literature review (SLR) was conducted, using databases such as Scopus, Web of Science, and SpringerLink between July and September 2025. The inclusion criteria were English-language empirical articles published between 2015 and 2025. The Mixed Methods Appraisal Tool (MMAT) was used to evaluate the quality of the literature, and NVivo was used for thematic data analysis. A total of 35 studies met the inclusion criteria. Four main themes emerged: (1) Growing customer interest in purchasing halal goods; (2) Supply chain mechanisms involving certification integrity and traceability; (3) Sustainability challenges such as cross-contamination and inconsistent regulation; (4) Market opportunities in non-Muslim countries, highlighting global awareness of halal product quality and safety. Despite challenges, the global halal market holds significant potential. Technologies like blockchain can improve transparency and traceability, while harmonizing global halal certification systems is crucial. To investigate the use of these technologies, further investigation is required Keywords: Halal Products, Supply Chain, Halal Certification, Global Market, Sustainability